2000
DOI: 10.1007/s002100000295
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of antidepressant drugs with enteric 5-HT 7 receptors

Abstract: In this study the functional interaction of the antidepressant drugs amitriptyline, mianserin, maprotiline, imipramine, fluoxetine and the putative antidepressant drug flibanserin has been studied on 5-HT7-mediated responses to 5-carboxamidotryptamine (5-CT) in the guinea-pig ileum. 5-CT induced a concentration-dependent inhibition of the contractile response to substance P (100 nM). Except for fluoxetine and flibanserin, all the antidepressants antagonized by different degrees the 5-CT inhibitory response wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
5
21
0
Order By: Relevance
“…55 Interestingly, mianserin, imipramine, amitriptyline and fluoxetine, a pharmacologically diverse range of antidepressants, behave as antagonists at enteric 5-HT 7 receptors. 61 This pharmacological finding corroborates the behavioural data that show 5-HT 7 antagonism producing antidepressant behavioural effects. In contrast, however, citalopram (a highly selective SRI) does not bind to the 5-HT 7 receptor at all.…”
Section: Role Of 5-ht In Regulating Hippocampal Neurogenesis: Can 5-hsupporting
confidence: 80%
“…55 Interestingly, mianserin, imipramine, amitriptyline and fluoxetine, a pharmacologically diverse range of antidepressants, behave as antagonists at enteric 5-HT 7 receptors. 61 This pharmacological finding corroborates the behavioural data that show 5-HT 7 antagonism producing antidepressant behavioural effects. In contrast, however, citalopram (a highly selective SRI) does not bind to the 5-HT 7 receptor at all.…”
Section: Role Of 5-ht In Regulating Hippocampal Neurogenesis: Can 5-hsupporting
confidence: 80%
“…Liu/Coupar/Irving The antidepressant drugs previously screened by Lucchelli et al [13] using the guinea-pig ileum 5-HT 7 model displayed similar antagonist profiles in the rat jejunum. Among these drugs, only mianserin produced a surmountable antagonism of 5-CT in the concentration range of 0.1-1 Ìmol/l, giving a pA 2 value of 8.22 B 0.33 (n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…This was to maintain uniformity with other published data so that results could be compared directly [9,10,13,16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 It is likely that these properties are related to the reductions in diarrhoea that have been reported in several clinical trials in patients with IBS, [14][15][16] and also to the ability of these drugs to increase gastrointestinal transit time. 26 Interestingly, it has been shown that administration of amitriptyline or fluoxetine to rats for a period of one month using non-psychiatric doses resulted in enhancement of the sensitivity of contractile intestinal muscle serotonin in vitro.…”
Section: Antidepressantsmentioning
confidence: 99%